Original articleIn vitro pharmacological evaluation of the radiolabeled C-terminal substance P analogue Lys-Phe-Phe-Gly-Leu-Met-NH2: Does a specific binding site exist? - Tomczyszyn, Aleksandra; Csibrany, Balazs; Keresztes, Attila; Mallareddy, Jayapal Reddy; Dyniewicz, Jolanta; Misicka, Aleksandra; Toth, Geza; Lipkowski, Andrzej W. (Folia Neuropathologica, 2014)
In the present paper, we report the synthesis, radiolabeling and comprehensive pharmacological evaluation of a C-terminally truncated tachykinin derivative, 3H-KFFGLM-NH2. The C-terminal fragments of endogenous tachykinins are pharmacophores responsible for interaction with the tachykinin receptors NK1, NK2 and NK3. The N-terminal fragments are responsible for modulation of receptor selectivity and interactions with other receptor systems. To evaluate and separate the function of an NK-pharmacophore from the activity of its parent neurokinin, KFFGLM-NH2 was synthesized in both tritiated and unlabeled forms. It has been proposed that the obtained NK-binding profiles of specific reference ligands and KFFGLM-NH2 differentiate monomeric and dimeric forms of NK receptors. We hypothesize that dimers of NK receptors could be specific receptor(s) for C-terminal fragments of all neurokinins as well as their C-terminal fragments, including H-KFFGLM-NH2. Dissociation of dimers into monomers opens access to additional allosteric binding sites. Fully elongated undecapeptide substance P interacts with both the “tachykinin pocket” and the “allosteric pocket” on the monomeric NK1 receptor, resulting in high and selective activation. However, C-terminal hexapeptide fragment analogues, recognizing only the “tachykinin pocket”, may have less specific interactions with all tachykinin receptors in both monomeric and dimeric forms.